Planet ape - Morris, Desmond; Parker, Steve 1952-. (Great Britain Mitchell Beazley, 2009)
Detail of the great apes, including: where they live, how they live and the challenges they face. Illustrations compare apes with human beings, including their anatomy, social life, physical and mental development, diet and communication.
Foreword -- Meet the great apes -- What is a great ape? -- Evolution of the primates -- Where do the great apes live? -- Family portraits -- Bornean orangutan -- Sumatran orangutan -- Western gorilla -- Mountain gorilla -- Chimpanzee -- Bonobo -- Prosimians -- Old World monkeys -- New World monkeys -- Gibbons -- Of apes and men -- Shared traits of the great apes -- The story of DNA -- Extinct ancestors -- Living relatives? -- Uniquely human -- How the human species advanced -- The hunted ape -- The performing ape -- Apes observed -- Apes studied in the wild -- Ape intelligence -- Apes and sign language -- Apes in experiments -- Ape anatomy -- Apes on the outside -- Size and shape -- Bones, bodies, and limbs -- Skeleton and posture -- Muscles and moving -- Faces -- Hands and feet -- Brains and nerves -- Senses -- Internal organs -- The daily meal -- Feeding and tool-use -- Essentials of diet -- Daily needs -- Diet and dentition -- A life of plants -- Foraging strategies -- Feeding routine : orangutan -- Meat-eating -- On the hunt -- Communication skills -- Why communicate? -- Visual signals -- Messages through sound -- Touch, scent, and smell -- Social life -- Family matters -- Living in numbers -- Apes alone -- Who's in charge -- Social climbing -- Playing -- Joining and leaving -- Territories -- Sex life -- How many mates? -- Starting out -- Courtship -- Breeding cycles -- Mating -- Pregnancy -- Birth and babies -- The stages of life -- Infancy -- Childhood -- Milestones of infancy -- Adolescence -- Adulthood -- Illness, injury, and death -- Growing threats -- Natural threats -- Habitat destruction -- Hunting and poaching -- Disease -- Warfare -- Not enough genes -- Saving planet ape -- Global efforts -- Charity work -- Ecotourism and community efforts -- Captive-breeding -- Rehabilitation and reintroduction -- How we can help -- Charities & organizations -- Index & acknowledgments.
Includes index.
ASP-1433g donated by Danny Galang
Keywords: Apes; Grands singes